Determinants of the Utilization of Electronic Medical Record (EMR) Systems by Healthcare Human Resources at Grandmed Hospital - Sirait, Reni Aprinawaty; Judika Silaban (JURNAL KESMAS DAN GIZI (JKG), 2025)
The implementation of Electronic Medical Records (EMR) has become one of the most significant innovations in health services, aiming to enhance efficiency, effectiveness, and quality of care in hospitals. This study seeks to analyze the determinants that influence the utilization of EMR by health personnel at Grandmed Hospital. Using a quantitative approach with a cross-sectional design, the study involved health workers as respondents to identify factors such as training, technical support, user perception, and system usability that affect the successful implementation of EMR. The findings indicate that adequate training, positive user perception, and strong management support significantly contribute to the optimal use of EMR. Furthermore, system design that aligns with workflow is also proven to reduce resistance and improve acceptance among health personnel. These results highlight that the successful implementation of EMR is not merely a matter of technology, but also requires readiness of human resources, supportive policies, and continuous evaluation to ensure its sustainability. This research is expected to serve as a reference for hospital management in strengthening EMR implementation strategies, so that the benefits of EMR can be maximized, including improving patient safety, streamlining clinical and administrative processes, and supporting data-based decision-making. Ultimately, strengthening these factors is an important step in achieving quality digital health services that are sustainable and adaptive to technological developments